Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Melakukan Perpindahan Merk Dari Merk IM3 Ke Merk Lain (Studi Kasus Pada Mahasiswa S1 FISIP Universitas Diponegoro Semarang) - Denny Okkyana Prihasni; Saryadi Saryadi; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the needs of consumers on the internet increasing. IM3 is one simcard which provides internet package, however there are several factors that cause consumers to switch to other brands. The purpose of this study was to determine the factors that influence consumers to make the switch from brand IM3 brand to another brand.This type of research is explanatory research. The sampling technique include nonprobability sampling technique is purposive sampling. The sample in this research were 100 respondents who are barchelor’s degree students of Social and Politic faculty Diponegoro University Semarang. Scale measurements using a Likert scale. In the analysis of the test used factor analysis with SPSS 20.Based on the analysis, the variable price, product quality, advertising, and lifestyle have a effect on the decision of brand switching. Lifestyle variable has the most impact amounted 28.8%. The variable of price has the effect amounted 15.3%. The variable of quality products has the effect amounted 7,8%. The variable of advertising has 26,3%.Conclusion of the research  shows the factors that influence consumers to make the switch from IM3 to another brand consists of price, quality of products, advertising, and lifestyle. Based on the results of the PT. Indosat, Tbk should establish the price which proper with benefit, product quality should be improved, clearer advertising messages, and more dynamic in following consumer lifestyle will need the internet.